Global Challenges of Current Building-Integrated Solar Water Heating Technologies and Its Prospects: A Comprehensive Review - Wan Afin Fadzlin; Md. Hasanuzzaman; Nasrudin Abd Rahim; Norridah Amin; Zafar Said (Energies, 2022)
Among the renewable energy resources, solar thermal is one of the technologies that significantly contribute to energy supply and reduce global greenhouse gas (GHG) emissions. Solar water heating (SWH) contributes a large proportion of the global solar thermal capacity, with 63% installation for domestic hot water (DHW) systems, 28% for large DHW systems, and the remaining 9% for other applications such as swimming pools heating, solar district heating, and space heating. Still, now, there are many challenges and limitations of those SWH technologies. The present work reviews the current challenges faced in the domestic SWH industry globally. The integration of thermal energy storage (TES) systems for better collector’s radiation absorption and overall performance are also highlighted. Many countries worldwide seem to face similar challenges within the SWH technologies and industry. It is proven that these challenges and limitations can hinder the global capacity of solar thermal utilization.